Práticas pedagógicas extraordinárias: análise de virtudes políticas de professores de biologia - Maria Lucia Yoshico Wakisaka (2008)
We investigate biology teachers' reports of educational practices that differ from routine practices and in which teachers and students feel motivated and happy. These practices were called extraordinary teaching practices. The practices were analyzed based on Hanna Arendt's concept of action. The aim of this analysis was to identify ethical commitments of teachers through the benefits that they seek conducting such activitieswith their studentes. We interviewed seven public high school teachers, all Biology Bachelors, with three to twenty-eight years of teaching experience. Analytical descriptions have been made to identify the incentives, challenges and results in the practices reported by teachers. These incentives, challenges and results were analyzed according to five political virtues that characterized these practices as action: courage,honor, prudence, cunning and freedom. The strengths identified in the action of the protagonists of educational practices are likely to be extraordinary given by any teacher. The actions reported and analyzed signal nuances of personal involvement in the teaching profession and show teachers as political actors of activities that give them humanity.